GIMI: the past, the present and the future. - Simpson, A; Power, D; Russell, D; Slaymaker, M; Bailey, V; Tromans, C; Brady, M; Tarassenko, L (2010)
In keeping with the theme of this year's e-Science All Hands Meeting--past, present and future--we consider the motivation for, the current status of, and the future directions for, the technologies developed within the GIMI (Generic Infrastructure for Medical Informatics) project. This analysis provides insights into how some key problems in data federation may be addressed. GIMI was funded by the UK's Technology Strategy Board with the intention of developing a service-oriented framework to facilitate the secure sharing and aggregation of heterogeneous data from disparate sources to support a range of healthcare applications. The project, which was led by the University of Oxford, involved collaboration from the National Cancer Research Institute Informatics Initiative, Loughborough University, University College London, t+ Medical, Siemens Molecular Imaging and IBM UK.